ANALYSIS AND INVESTIGATION OF CHARACTERISTICS OF QUADRATIVE PHASE MODULATION AFFECTING INTERFERENCE-RESISTANT RECEPTION - A.B.Jabborov (Galaxy International Interdisciplinary Research Journal, 2022)
The article investigates the main regularities of noise-immune formation of quadrature phase modulation. Mathematical models, diagrams of the QPSK signal and the results of a theoretical study of the dependence of the bit error probability on Eb / N0, to ensure noise-immune reception of digital television signals.